Value co-creation in sport entertainment between internal and external stakeholders. Issue 11 (3rd June 2019) - Erhardt, Niclas; Martin-Rios, Carlos; Chan, Elisa
Abstract : Purpose: Co-creation as a collaborative process between organizations and customers generates unique value for both internal and external stakeholders for the company. Research generally examines and portrays customer-company co-creation as a balanced and harmonious relationship. However, a successful co-creation strategy involves understanding the shared interests of the parties and resolving tensions between internal and external stakeholders to avoid co-destruction. This study aims to draw on the intersection of organizational behavior and marketing literature and to examine shared interests and conflicting tensions involved in the co-creation in the context of sports entertainment. This context allows the researchers to unpack and present a more complex process of co-creation that fosters co-creativity and innovation. Design/methodology/approach: Based on a qualitative case-based approach of a major university in the USA, the authors draw on interviews and observations from their athletic administration and fans engaged in a men's Division I team through an entire season. Findings: This qualitative study illustrates an alternative, more complex dilemma of co-creating emotional and symbolic value based on shared interests while reconciling conflicting internal and external stakeholder interests. The findings suggest a tug of war based on tensions, where management adopted contrasting managerial strategies ranging from attempting to reconcile tension through organic co-creation to controlled manufactured creation. Research limitations/implications: Emotional and symbolic game experience value is an interdependent process which cannot be created without consumer engagement. Both emotional and symbolic values are enhanced during games to the extent consumers perceive participation in the creative pre-game stages. Originality/value: This study draws on sports entertainment to identify sources of tension in co-creation and discuss type of solutions among internal and external stakeholders.